PWE-047 The impact of infliximab (ifx) therapeutic drug monitoring on decisions made in a virtual biologics clinic for ibd. (17th June 2017) - Selinger, C; Lenti, M; Clark, T; Rafferty, H; O'Connor, A; Ahmad, T; Hamlin, J
Abstract : Introduction: Virtual biologics clinics (VBC) are used to review annually patients receiving biological therapy. Decisions on continuing, switching or stopping therapy are based on review of clinical symptoms, disease history and investigations. Therapeutic drug monitoring (TDM) of Infliximab trough levels (ITL) and anti-drug antibodies (ADA) has previously not been universally available in the UK. The aim of this study was to assess whether access to TDM influences decision making within VBC. Method: All IBD patients receiving Infliximab maintenance therapy were reviewed and two treatment decisions were recorded. The first decision was based on assessment of all clinical details but clinicians remained blinded to ITL and ADA data (Biohit assay). An administrator revealed ITL and ADA data and clinicians formed a second decision incorporating TDM. Decisions were standardised to: A - continue without change B -shorten infusion interval/increase IFX dose C - lengthen infusion interval D - stop IFX E - other. Results: Of 201 patients reviewed TDM data were available for 191 (mean 40y old, 57% male). Diagnoses were Crohn's disease in 160, ulcerative colitis in 18 and IBD-U in 13 cases. Mean duration of IFX treatment was 4 years (minimum 6 months), 57% received co-therapy with immunomodulator and 38% had shortened infusion intervals. Disease activity was remission in 70%, mild in 19%, moderate in 10% and severe in 1%. ITL were sub-therapeutic in 25% (<1.8 mg/L), therapeutic in 61% and supra-therapeutic in 14% (>7 mg/L); mean ITL was 3.85 mg/L. ADA were detected in 30% and were >50 AU/ml in 14%. Blinded treatment decisions were changed on unblinded review in 56 cases (29%, table 1, chi-square test: p<0.0001). Knowledge of ITL and ADA led to 7 patients receiving higher dose IFX or more frequent infusions whereas 33 patients were able to dose de-escalate or stop IFX therapy. Decision: Conclusion: Basing decisions on TDM rather than clinical acumen alone led to change in 29%. An additional 23 patients discontinued therapy (undetectable ITL + high ADA). This represents a considerable cost saving and reduces the exposure to potentially toxic therapies. Routine TDM should be considered as an integral part of VBC. Disclosure of Interest: None Declared